P2x1 Receptors Localized in Lipid Rafts Mediate Atp Motor Responses in the Human Vas Deferens Longitudinal Muscles - Garcia Huidobro-Toro, J; Donoso-Gomien, M (Society for the Study of Reproduction, 2014)
To assess the role of the P2X1 receptors (P2X1R) in the longitudinal and circular layers of the human vas deferens, ex vivo-isolated strips or rings were prepared from tissue biopsies to record isometric contractions. To ascertain its membrane distribution, tissue extracts were analyzed by immunoblotting following sucrose gradient ultracentrifugation. ATP, alpha,betamethylene ATP, or electrical field stimulation elicited robust contractions of the longitudinal layer but not of the circular layer which demonstrated inconsistent responses. Alpha,betamethylene ATP generated stronger and more robust contractions than ATP. In parallel, prostatic segments of the rat vas deferens were examined. The motor responses in both species were not sustained but decayed within the first minute, showing desensitization to additional applications. Cross-desensitization was established between alpha,beta-methylene ATP or ATPevoked contractions and electrical field stimulation-induced contractions. Full recovery of the desensitized motor responses required more than 30 min and showed a similar pattern in human and rat tissues. Immunoblot analysis of the human vas deferens extracts revealed a P2X1R oligomer of approximately 200 kDa under nonreducing conditions, whereas dithiothreitoltreated extracts showed a single band of approximately 70 kDa. The P2X1R was identified in ultracentrifugation fractions containing 15%-29% sucrose; the receptor localized in the same fractions as flotillin-1, indicating that it regionalized into smooth muscle lipid rafts. In conclusion, ATP plays a key role in human vas deferens contractile responses of the longitudinal smooth muscle layer, an effect mediated through P2X1Rs. © 2014 by the Society for the Study of Reproduction, Inc.